Mini Poster Education on Toddler Nutrition Toward Mother’s Knowledge and Attitudes in Batusari Brebes Village - Milhatul Azizah; Rakhmat Susilo (Universitas Airlangga, 2025)
Background: Nutrition is important to support the growth and development of toddlers. Toddlers are an age group that is very susceptible to nutritional disorders because, at the toddler age, the nutrition required is greater for growth and development. Objectives: This research aimed to determine the effect of educational mini posters on toddler nutrition on mothers' knowledge and attitudes in Batursari Village. Methods: This research used a quantitative design with a pre-experimental design, with one group, a pretest, and a post-test. There were 40 samples in the research of mothers with toddlers aged 1-5 years. Samples were taken using total sampling. The instrument used was a questionnaire and the test used was the Wilcoxon test. Results: The results of the Wilcoxon statistical test obtained a p-value of 0.000, which means p < 0.05, to determine the results of the intervention before and after being given education using mini-poster media. The results of the study showed that the average knowledge before being given the mini-poster intervention obtained a value of 4.70, after being given the mini-poster intervention the knowledge score was 9.53, and the average attitude score before being given the mini-poster intervention was 33.48 And after being given the mini-poster intervention the attitude score was 47.75. Conclusion: There is a difference in the effect of providing education to mothers of toddlers using media such as posters compared to providing education without using media.